Bmi-1: A master regulator of head and neck cancer stemness - Herzog, Alexandra E.; Somayaji, Ritu; Nör, Jacques E. (Frontiers in Oral Health, 2023)
Head and neck cancers are composed of a diverse group of malignancies, many of which exhibit an unacceptably low patient survival, high morbidity and poor treatment outcomes. The cancer stem cell (CSC) hypothesis provides an explanation for the substantial patient morbidity associated with treatment resistance and the high frequency of tumor recurrence/metastasis. Stem cells are a unique population of cells capable of recapitulating a heterogenous organ from a single cell, due to their capacity to self-renew and differentiate into progenitor cells. CSCs share these attributes, in addition to playing a pivotal role in cancer initiation and progression by means of their high tumorigenic potential. CSCs constitute only a small fraction of tumor cells but play a major role in tumor initiation and therapeutic evasion. The shift towards stem-like phenotype fuels many malignant features of a cancer cell and mediates resistance to conventional chemotherapy. Bmi-1 is a master regulator of stem cell self-renewal as part of the polycomb repressive complex 1 (PRC1) and has emerged as a prominent player in cancer stem cell biology. Bmi-1 expression is upregulated in CSCs, which is augmented by tumor-promoting factors and various conventional chemotherapies. Bmi-1+ CSCs mediate chemoresistance and metastasis. On the other hand, inhibiting Bmi-1 rescinds CSC function and re-sensitizes cancer cells to chemotherapy. Therefore, elucidating the functional role of Bmi-1 in CSC-mediated cancer progression may unveil an attractive target for mechanism-based, developmental therapeutics. In this review, we discuss the parallels in the role of Bmi-1 in stem cell biology of health and disease and explore how this can be leveraged to advance clinical treatment strategies for head and neck cancer.